Effects of spatial characteristics of footsteps sounds and non-acoustic factors on annoyance in lightweight timber buildings - Frescura, Alessia; Lee, Pyoung Jik; Soeta, Yoshiharu; Ariki, Ayaka (Building and environment, 2022)
This study investigates the effect of spatial characteristics of footsteps sound from upstairs in wooden residential buildings together with the influence of non-acoustic factors on annoyance ratings. Footsteps sound were recorded in the laboratory, where a typical lightweight timber joists floor is located between the source and receiving room. Two adults walked on the floor over three different paths (figure-of-eight, straight, and walking on the spot) at two different paces (very slow and normal). The spatial features of the recordings were quantified in terms of the magnitude of interaural cross-correlation (IACC) function. A total of 46 participants were recruited and they assessed their subjective annoyance after exposure to noise under laboratory conditions. During the laboratory experiments, 360-degree pictures of a living room during daytime or night-time were presented via a Head-Mounted Display (HMD). In addition, the participants were asked to answer questions concerning noise sensitivity, chronotype, and attitude towards neighbours. Results highlighted that IACC had a significant effect on annoyance, showing an increase in annoyance with increasing IACC. Footsteps at a very slow pace were more annoying than those at a normal pace. It was also found that annoyance ratings with a presentation of the living room during daytime were greater than those with a presence of the night-time living room. Furthermore, noise sensitivity, circadian rhythm, and attitude towards neighbours of participants were significant in moderating annoyance ratings. •IACC of upstairs footsteps sound significantly affected annoyance ratings.•The pace of the walker has a significant effect on annoyance ratings.•Significant differences in annoyance ratings were found between daytime and night-time conditions.•Self-assessed noise sensitivity, attitude towards neighbours, and circadian rhythm type influenced annoyance ratings.